Applications of 3D printing in the management of severe spinal conditions. (June 2017) - Provaggi, Elena; Leong, Julian J H; Kalaskar, Deepak M
The latest and fastest-growing innovation in the medical field has been the advent of three-dimensional printing technologies, which have recently seen applications in the production of low-cost, patient-specific medical implants. While a wide range of three-dimensional printing systems has been explored in manufacturing anatomical models and devices for the medical setting, their applications are cutting-edge in the field of spinal surgery. This review aims to provide a comprehensive overview and classification of the current applications of three-dimensional printing technologies in spine care. Although three-dimensional printing technology has been widely used for the construction of patient-specific anatomical models of the spine and intraoperative guide templates to provide personalized surgical planning and increase pedicle screw placement accuracy, only few studies have been focused on the manufacturing of spinal implants. Therefore, three-dimensional printed custom-designed intervertebral fusion devices, artificial vertebral bodies and disc substitutes for total disc replacement, along with tissue engineering strategies focused on scaffold constructs for bone and cartilage regeneration, represent a set of promising applications towards the trend of individualized patient care.